Pattern Identification in the Buffer Level as a Tool to Identify Inefficiencies in a Pharmaceutical Packaging Line. (6th November 2014) - Carlo, Filippo De; Arleo, Maria Antonietta; Tucci, Mario
The pharmaceutical industry manufactures products of the highest importance to society. Keeping the cost of the production of medicines at low levels is very important to ensure better accessibility to medicines, especially if we think of the less wealthy countries of the planet. Among the production steps that need to be carefully monitored and optimized, the final packaging phase is sometimes considered less important. This is a mistake, because, being the last stage of production, it can negatively affect all other upstream phases. The aim of this work is to evaluate whether the throughput and work in process diagrams can be useful for the rapid and effective control of the line activity. The result was positive, given that, with the help of a case study, we could identify four patterns corresponding to the same number of typical operating conditions of the line, either regular or altered. After identifying the typical pattern of the line studied, the use of such diagrams can be employed either in real-time or retrospectively for an accurate analysis of the behaviour of the production line.